Digital Footprint of Violence: Bibliometric Analysis of Online Gender-Based Violence with Vosviewer and Scopus - Rakhmawati, Dini; Saptadi, Heri; Ratu, Bau; Suryadi; Basir Jarah Anilon (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to map and analyze the scientific landscape of online gender-based violence (OGBV) comprehensively through a bibliometric approach, utilizing the Scopus database and the VOSviewer visualization tool. The goal is to identify trends in topic evolution, key research focus clusters, and prospective research gaps. This method quantifies and visualizes the research structure of OGBV from 2016 to 2025. The results of the Co-Keyword analysis show that the scientific literature is very focused on two main concepts: "cyber violence" and "cyber-bullying". Research has shifted from an initial focus on adolescent cyber-bullying to more gender-specific contemporary and social issues, such as "hate speech" and "online harassment" on "social media". The cluster analysis grouped the research into three main areas: 1) Studies on Victims and Their Impacts (focusing on psychology and quantitative methodologies), 2) Digital Contexts and Forms of Violence (focusing on social media and specific violence), and 3) Gender-Based Violence Relationships and Aspects (focusing on perpetrators, prevention, and online-offline relationships). The main research gap identified in the prevention area, where the term density remains low, underscores the urgency of developing effective interventions and strategies for OGBV. Keywords: bibliometrics, online gender-based violence, vosviewer, cyber violence